Organic agriculture in Kenya : Focus on: Current approaches in chemical ecology using regionally adapted sustainable methods - Winter, Eva; Justus Liebig University Giessen (My University, 2013)
Kenya is an African developing country situated at the equator ranking 157 th of 177 countries in the human development index. Agriculture is next to tourism the most important economic sector with 24 % of the GDP. Poverty prevalence is highest with small holder farmers. A promissing approach to reduce this precarious condition is the implementation of organic agriculture. 1. Establishment of certified organic cash crop production for a domestic and/or an export market and 2. dissemination of common methods in organic agriculture to subsistently living small holder farmers are the two major strategies of the approach. Both have different positive impacts regarding poverty reduction. This Bachelor thesis focuses on the science-based push-pull project of the second strategy: In South western Kenya, the "push-pull" cropping system for maize and sorghum production in subsistence farming was developed. It is a farming system which exploits the allelopathic defense reactions of indigenous plants against the major pests stem borers and the parasitic Striga weed in Subsaharan Africa. The first experiment of this thesis strives to better understand one of the interactions within the cropping system. It is investigated if the legume Desmodium intortum which is commonly used in the push-pull cropping system induces a defense in Zea mays varieties against stem borer moths (Lepidoptera: Crambidae).The second experiment concerns the common corn pest Diabrotica virgifera virgifera LeConte (Chrysomelidae)which is one of the major threats to modern corn production. Due to favourable conditions in East Africa it is probable that it will migrate to this region. The experiment was designed to investigate with the help of sex pheromone traps if D. virgifera virgifera has already reached the South western region Nyanza in Kenya.

Kenia ist ein afrikanisches Land am Äquator, das Platz 157 von 177 Ländern im Human Development Index einnimmt. Landwirtschaft ist neben Tourismus der größte ökonomische Sektor mit einem Anteil von 24 % des BIPs. Armut ist unter Kleinbauern am verbreitesten. Die Implementierung von ökologischer Landwirtschaft hat sich als ein vielversprechender Ansatz der Armutsreduzierung erwiesen. Hierbei sind die zwei Hauptstrategien 1. die Etablierung eines zertifizierten Ökolandbaus für Binnen- und/oder Exportmarkt und 2. die Verbreitung gängiger Methoden des Ökolandbaus bei subsistent lebenden Kleinbauern. Beide Strategien haben unterschiedliche positive Auswirkungen auf ländliche Entwicklung.Bei dieser Bachelor-Thesis steht die Nutzung ökologischer Prinzipien in kleinbäuerlicher Landwirtschaft im Fokus. Im "push-pull" Projekt, das im Südwesten Kenias seinen Ursprung hat, wurde eine Anbausystem für Mais und Sorghumhirse entwickelt. Das Anbausystem nutzt durch eine Mischkultur allelopathische Abwehrreaktionen indigener Pflanzen gegen wichtige Schädlinge inSubsahara-Afrika wie Stängelbohrer (Lepidoptera: Crambidae) und parasitäre Striga-Gewächse.Im ersten experimentellen Teil der Thesis wird eine Interaktion zwischen der Kulturpflanze Zea mays und einer bewährten Untersaat Desmodium intortum genauer beleuchtet. Es wird untersucht, ob Desmodium intortum einen Abwehrmechanismus gegen Stängelbohrer in verschiedene Maissorten induziert.
Keywords: Kenia; Chemische Ökologie; Mischkultur; Entomologie; Stängelbohrer; Diabrotica v. virgifera; Kenya; chemical ecology; push-pull; entomology; stemborers; Diabrotica v. virgifera; ddc:630